Effect of different cell sheet ECM microenvironment on the formation of vascular network. Issue 5 (October 2016) - Chen, Jia; Zhang, Dan; Li, Qin; Yang, Dan; Fan, Zengjie; Ma, Dongyang; Ren, Liling
Highlights: In this study we show a promising strategy to develop prevascularized bone grafts for bone tissue regeneration. We used cell sheet engineering technique to construct osteogenic differentiated cell sheet and undifferentiated cell sheet, respectively. Then we seeded human umbilical vein endothelial cells (HUVECs) onto the surface of the two sheets at different seeding densities to fabricate pre-vascularized cell sheets. Our results indicated that the two sheets facilitated the alignment of HUVECs and promoted the formation of vascular networks, while differentiated cell sheet promoted significant vascular networks. Abstract: The repair and reconstruction of large bone defects remains as a significant clinical challenge mainly due to the insufficient vascularization. The prefabrication of vascular network based on cell sheet technique brings a promising potential for sufficient vascularization due to rich extracellular matrix (ECM) of cell sheets. However, the effect of different cell sheet ECM micro-environment on the formation of a vascular network has not been well understood. Here our goal is to study the effect of different cell sheets on the formation of a vascular network. First we cultured human bone marrow mesenchymal stem cells (hBMSCs) under two culture conditions to obtain osteogenic differentiated cell sheet (ODCS) and undifferentiated cell sheet (UDCS), respectively. Then the human umbilical vein endothelial cells (HUVECs) were seeded onto the surface of the two sheets at different seeding densities to fabricate pre-vascularized cell sheets. Our results indicated that the two sheets facilitated the alignment of HUVECs and promoted the formation of vascular networks. Quantitative analysis showed that the number of networks in ODCS was higher than that in the UDCS. The ECM of the two sheets was remodeled and rearranged during the tubulogenesis process. Furthermore, results showed that the optimal seeding density of HUVECs was 5 × 10 4 cell/cm 2 . In summary, these results suggest that the vascularized ODCS has a promising potential to construct pre-vascularized tissue for bone repair.